Peran Polres Malang Kota dalam Menanggulangi Pengeroyokan Perguruan Pencak Silat Persaudaraan Setia Hati Terate terhadap Warga Kecamatan Sukun - Ristanti, Enny; Alfayed, Teddy Pradana; Siahaan, Sita Agustina (University of Merdeka Malang, 2023)
The police's duty is to maintain the stability of community security as the first line of defense in handling conflicts that occur in the surrounding environment. The case that occurred in Malang City was the assault by a silat martial arts school (Persaudaraan Setia Hati Terate) on residents of Sukun district, which often harmed the community, resulting in victims and material losses. Based on this, the author will analyze the triggering factors of the assault and how the efforts of the police to handle the assault to prevent the conflict from spreading, as well as the obstacles faced by the police in handling the assault and law enforcement for violent criminal acts. The research method used is empirical, employing juridical and sociological approaches. Data collection is based on interviews with the Malang City Police Force, namely the Criminal Investigation Body (Badan Reserse Kriminal or Bareskrim), and documentation. The interview results show that the efforts made by the Police in handling this assault involve preventive, repressive, and preemptive measures. The Bareskrim of Malang City, when an assault occurs, takes a repressive stance by arresting the perpetrators to deter them and prevent members of the silat martial arts school, especially Persaudaraan Setia Hati Terate, from engaging in harmful activities.